Enhancing suicide prevention outreach via mobile‐enabled website design. Issue 2 (20th April 2021) - Slay, Patrick D.; Castille, Kristina W.; Hong, Esther; Polizzi, Nicholas; Hoyt, Tim
Abstract: Online outreach campaigns are a potential public health method for reaching service members at risk for suicide. The Real Warriors Campaign website underwent a full redesign in 2019 to enhance its ability to provide crisis resources and increase engagement by adopting a mobile‐first strategy and implementing a responsive framework, meaning the site renders properly on all devices, including desktop, tablets, and mobile. Usability testing with end‐user service members led to several innovations on the website, including a one‐click banner that directly linked users on their mobile phones to crisis resources, the redesign of menus and content to better display on mobile devices, and promoting use of website resources through gateway topics. Comparing the 6 months before and after the mobile redesign showed significant increases in new mobile users, pages viewed on mobile devices, and new users coming to the site through social media. There was also a significant increase in specific help‐seeking actions by users, including use of referral links and live chat, as well as 200 individuals accessing crisis phone lines through new one‐click dialing banners. Suicide prevention campaigns should continue to optimize their online presence to reach groups at risk. This study of the website redesign from the Real Warriors Campaign illustrates several best practices in digital outreach as applied to suicide prevention, including leveraging usability testing, synching outreach material with social media, and ensuring mobile compatibility.